Analysis of the Movement-Inducing Effects of Music through the Fractality of Head Sway during Standstill. Issue 6 (1st November 2020) - González Sánchez, Victor; Żelechowska, Agata; Jensenius, Alexander Refsum
Abstract: The links between music and human movement have been shown to provide insight into crucial aspects of human's perception, cognition, and sensorimotor systems. In this study, we examined the influence of music on movement during standstill, aiming at further characterizing the correspondences between movement, music, and perception, by analyzing head sway fractality. Eighty seven participants were asked to stand as still as possible for 500 seconds while being presented with alternating silence and audio stimuli. The audio stimuli were all rhythmic in nature, ranging from a metronome track to complex electronic dance music. The head position of each participant was captured with an optical motion capture system. Long-range correlations of head movement were estimated by detrended fluctuation analysis (DFA). Results agree with previous work on the movement-inducing effect of music, showing significantly greater head sway and lower head sway fractality during the music stimuli. In addition, patterns across stimuli suggest a two-way adaptation process to the effects of music, with musical stimuli influencing head sway while at the same time fractality modulated movement responses. Results indicate that fluctuations in head movement in both conditions exhibit long-range correlations, suggesting that the effects of music on head movement depended not only on the value of the most recent measured intervals, but also on the values of those intervals at distant times.